تطبيق الطريقة الانتقائية في تحقيق الأهداف المكتوبة من الحكومة الخاصة في تعليم اللغة العربية بالمدرسة الثانوية الإسلامية الحكومية جمبر الأولى بالقسم الديني للسنة الدراسية 2019 - Zainuri Zainuri (Al-Fusha : Arabic Language Education Journal, 2020)
Eclectic method is when a teacher combines a number of methods and selects the appropriate methods based on the learning condition. According to the experts of eclectic method, there is no appropriate learning method for all learning purposes, students, teacher and all foreign language learning aspects. No method is perfect. Each method has advantages and disadvantages. The problem of the research is how the application of eclectic method in achieving the purposes set by the government in Arabic learning in terms of grammar, classical book-reading learning, and oral learning (speaking) at MAN 1 Jember religion program in 2019. The purpose of this research is describing the application of eclectic method in achieving the purposes set by the government in Arabic learning in terms of grammar, classical book-reading learning, and oral learning (speaking) at MAN 1 Jember religion program in 2019. The research used in the research is descriptive qualitative method. It analyzes the application of eclectic method in achieving the target set by the government in Arabic learning at MAN 1 Jember religion program in 2019. The data collection method used by the researcher is purposive sampling. The result of the research is a learning method used for learning Arabic grammar which combines speech, memorizing, drill, audio-lingual, nahwu-tarjamah, inductive, and peer-learning methods. Classical book-reading learning includes speech, memorizing, drill, audio-lingual, nahwu-tarjamah, answer-and-question, peer-learning, and sorogan methods, while oral learning (speaking) includes speech, direct, audio-lingual, memorizing, and role-play methods.